Reconstructing Criminal Liability in Trademark Law: Lessons from Indonesia and Spain - I Gede Agus Kurniawan; Ni Ketut Supasti Dharmawan; Putu Aras Samsithawrati; Anak Agung Ayu Ngurah Sri Rahayu Gorda; Antonio Gutiérrez-Pozo (Universitas Negeri Semarang, 2026)
This study examines the construction of criminal liability in trademark law through a comparative analysis between Indonesia and Spain. The main problem addressed is the limited effectiveness of Indonesia’s criminal trademark enforcement under Law Number 20 of 2016 on Trademarks and Geographical Indications, particularly due to its complaint-based offense model, unclear formulation of mens rea, limited scope of actus reus, and the absence of explicit corporate criminal liability and asset forfeiture mechanisms. The purpose of this research is to identify the similarities and fundamental differences in criminal liability frameworks in both jurisdictions and to formulate an ideal reconstruction model for Indonesia based on Spain’s best practices. This study employs normative legal research, drawing on conceptual and comparative approaches, by analyzing primary legal materials, legal doctrines, and relevant academic literature. The findings show that Spain provides a more coherent and effective criminal enforcement system through the integration of trademark crimes into the Código Penal, the application of public offenses, the requirement of commercial intent, the recognition of aggravated offenses, and explicit corporate criminal liability supported by additional penalties such as confiscation and business closure. In contrast, Indonesia’s current framework remains fragmented and less responsive to organized and digital-based trademark counterfeiting. This study concludes that Indonesia must reconstruct its criminal trademark provisions by shifting towards a differentiated public-offense model, strengthening the formulation of intent and commercial purpose, expanding digital enforcement coverage, incorporating protection for well-known unregistered marks, and establishing corporate criminal liability with comprehensive sanctions to ensure effective and proportional trademark protection aligned with international standards.